Communion : finding my way back to faith - Vance, J. D. (Harper, an imprint of HarperCollinsPublishers, 2026)
"[A]n intimate account of why Vice President JD Vance strayed from the Christianity of his youth and what led him back to faith. Communion is a spiritual exploration of what it means to be a Christian in all the seasons of life JD Vance has experienced -- as a child, a young man, a husband, a father, and a leader. Picking up in some ways where Hillbilly Elegy left off, Communion recounts how Vance's pursuit of material privileges ultimately led him into a secular wilderness. Communion reveals how Vance regained his faith and discusses his conversion to Catholicism, how his faith guides his work in public life, and how it shapes his thoughts about the future." --